2018
DOI: 10.4236/ajibm.2018.812154
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Risk Management: A Review of Thirteen Years of Research

Abstract: This paper performs a systematic literature review on supply chain risk management (SCRM). This review analyzes 133 articles published between 2005 and the first quarter of 2018. Its main purpose is to identify the developed strategies used to mitigate risks and improve supply chain performance. It appears that there is heterogeneity in the developed strategies and that quantitative methods simulation/modeling are the most used by researchers to mitigate supply chain risks (SCR). Although emphasis is made on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 156 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…, 2021; Munir et al. , 2020; Elock Son, 2018). The food supply chain is widely known for its vulnerability to environmental and social uncertainties (Davis et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021; Munir et al. , 2020; Elock Son, 2018). The food supply chain is widely known for its vulnerability to environmental and social uncertainties (Davis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Supply chain is the veins of the global economy and society (Ivanov, 2020). In a dynamic global context, a supply chain is known to be vulnerable to surrounding fluctuations (Marcos et al, 2021;Munir et al, 2020;Elock Son, 2018). The food supply chain is widely known for its vulnerability to environmental and social uncertainties (Davis et al, 2021;Yontar and Ers€ oz, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SCRM is a popular research area, and interest in this subject has grown (Ceryno et al, 2013). Numerous literature reviews have confirmed the importance and extent of SCRM over the years (Tang, 2006;Khan et al, 2008;Manuj & Mentzer, 2008;Rao & Goldsby, 2009;Tang & Nurmaya Musa, 2011;Colicchia & Strozzi, 2012;Sodhi et al, 2011;Ceryno et al, 2013;Fahimnia et al 2015;Ho et al, 2015;Snyder et al, 2015;Rajagopal et al, 2017;Prakash et al, 2017;Bugert & Lasch, 2018;Elock Son, 2018;Seipp et al, 2020;Shekarian & Mellat Parast, 2020). Tang (2006), based on the definitions of SCRM, makes a distinction between two dimensions (i) Supply chain risks and disruptions; and (ii) the Mitigation Approach concerning supply management, demand management and, most importantly, in our context, information management.…”
Section: Introductionmentioning
confidence: 99%